(untitled) (KULT_online, 2019)
In the conference volume Eine Fotografie. Über die transdisziplinären Möglichkeiten der Bildforschung, edited by Irene Ziehe and Ulrich Hägele, authors with various professional backgrounds, academic as well as non-academic, present their research results. 23 contributions are dedicated to photography and scientific picture analysis on an interdisciplinary basis. By outlining methodological approaches as well as giving examples of interpretations, the authors demonstrate how photographs with unknown design and contexts of origin are analyzed and interpreted. Thereby they provide a common foundation for a better understanding of the inherent informational contents of photographs. In the age of the knowledge society, described best by the strengthened use of new media as well as photographs, the ability to critically scrutinize and interpret the latter is vital. This publication is an inspiration arousing curiosity for the intensification of scientific research in this field of study and raising awareness for the need to introduce these new aspects into the public discourse.